Prinsip Kerahasiaan dan Objektivitas dalam Kaitan Penggunaan Hasil Tes Asesmen Psikologi pada Bidang Bimbingan dan Konseling di Sekolah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study discusses the importance of Guidance and Counseling (BK) activities in schools, which must be carried out by competent BK teachers or counselors. Referring to the Ministry of Education and Culture Regulation No. 111 of 2014, the presence of trained BK teachers is vital in helping students overcome academic and emotional challenges. This research aims to explore the practices of BK teachers in maintaining the confidentiality and objectivity of psychological assessment results, as well as to identify the obstacles they face. The method used is qualitative research through literature review, with data collection conducted purposively and using snowball techniques. The results indicate that ethical principles such as confidentiality, voluntariness, and openness are applied by BK teachers at school, creating a safe environment for students. However, BK teachers with non-BK educational backgrounds still have limited understanding of the code of ethics. These findings emphasize the need for enhancing BK teachers' competencies to provide more effective services in shaping students' ethics and morals and supporting their character development.